Men's anti-queer violence: the enduring impact of colonial era sex and gender binaries - Graaff, Karen (Interconnecting the violences of men, 2025)
Men’s violence against queer people is often taken as separate from gendered or gender-based violence, described as a hate crime, ‘gay-bashing’, ‘homophobic2 rape’, or homophobia/transphobia, as a specific violation of a marginalised group’s rights, rather than part of the continuum of men’s violence. Yet, this is problematic. First, it erases the gendered nature of the violence: that it is overwhelmingly perpetrated by men, specifically because of their beliefs about what are considered ‘acceptable’ sexes, genders and sexualities, and their adherence to norms which place cis-gendered, heterosexual men in positions of superiority. Second, it ignores interconnections with colonial, religious, and racial violence, particularly arising out of colonial efforts to create sex and gender binaries to differentiate white colonialists from indigenous and colonised populations. This chapter highlights how the colonial emphasis on separating and defining two different sexes and genders has enabled and encouraged men’s historical and current violence against queer people, as well as how this has been impacted by religion.